2015
DOI: 10.1016/j.bpj.2015.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Automated Analysis of Single-Molecule Photobleaching Data by Statistical Modeling of Spot Populations

Abstract: The number of fluorophores within a molecule complex can be revealed by single-molecule photobleaching imaging. A widely applied strategy to analyze intensity traces over time is the quantification of photobleaching step counts. However, several factors can limit and bias the detection of photobleaching steps, including noise, high numbers of fluorophores, and the possibility that several photobleaching events occur almost simultaneously. In this study, we propose a new approach, to our knowledge, to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 38 publications
(54 reference statements)
0
40
0
Order By: Relevance
“…The slower the decrease of the number of spots relative to the decrease of the intensity, the larger the number of fluorophores per spot. 262 Yet another approach is to count molecules by means of photon arrival statistics. 263,264 This technique exploits the photon antibunching effect, which essentially states that a single emitting quantum system (a fluorophore in this case) emits photons one at a time.…”
Section: The Counting Problemmentioning
confidence: 99%
“…The slower the decrease of the number of spots relative to the decrease of the intensity, the larger the number of fluorophores per spot. 262 Yet another approach is to count molecules by means of photon arrival statistics. 263,264 This technique exploits the photon antibunching effect, which essentially states that a single emitting quantum system (a fluorophore in this case) emits photons one at a time.…”
Section: The Counting Problemmentioning
confidence: 99%
“…including prior information about dye photo-physics [136]. Here, published datasets were analyzed, [137]. Counting the number of photo-bleaching steps has been extensively used to quantify membrane receptors and ion channels in the plasma membrane with typical stoichiometries on the order of 4-5 [11].…”
Section: Intensity-based Counting (Ibc)mentioning
confidence: 99%
“…To get insights into this process, we compared two different recombinant ligands, the natural soluble CD95L (sCD95L), a weak apoptosis inducer (23), and the isoleucine zipper-fused ligand (IZ-sCD95L), which is a strong apoptosis inducer (29) (53). We have previously shown that sCD95L and IZ-sCD95L are trimeric at the population level even in the picomolar range (27), a result that we validated here by comparing the brightness of mCherry-sCD95L, mCherry-IZ-sCD95L and mCherry-IZ to the one of mCherry alone by fluorescence correlation spectroscopy (FCS) (Fig. S7A).…”
Section: Equal Cd95 Receptor Occupancy With Scd95l and Iz-scd95l Tranmentioning
confidence: 99%
“…The extracellular domain of CD95L can be cleaved by proteases (20) (21) (22) and the soluble product, sCD95L, is a weak inducer of apoptosis that can block the activity of the membrane form (23) (20) (24) (25). Using gel filtration (25), X-ray crystallography (26) and single molecule fluorescence microscopy (27) it was shown that sCD95L forms a trimer. Two types of modifications can transform sCD95L into a strong apoptosis inducer: its secondary multimerization using antibodies (24) (28) or its recombinant fusion to a trimerization domain, like the isoleucine zipper (IZ) (29) or the foldon that is part of the protein fibritin from the bacteriophage T4 (30).…”
Section: Introductionmentioning
confidence: 99%